ISLAMIC PERSPECTIVE OF LEADERSHIP - Muhtar Solihin, Prof. Dr. H. (IJRDO - Journal of Social Science and Humanities Research, 2017)
Islam has a close relationship with the leadership, because Islam will be strong leadership, and vice versa leadership goes well when the values of Islam came with the leadership system. For that leadership is a must. The essence of leadership in Islam is the power to govern the people with good values, ideals, and responsibility, so that adherence to the leader is mandatory. Islam has the concept of the country's leadership for the implementation of the teachings. Therefore the duty of Islamic rule, is a substantial part of the teachings of Islam. State leadership system in Islam can take the form of the Khilafah (for Sunnis) or Imamate (for the Shiites). Both the governmental system of determining its leaders through the electoral process. People who become leaders of the country must have intelligent criteria, admirable, honest, and trustworthy, because these criteria can guarantee fulfilled duties, obligations, the purpose of government.